2017
DOI: 10.1038/s41598-017-05735-w
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Fasciola hepatica fatty acid binding protein suppresses toll-like receptor stimulation in response to multiple bacterial ligands

Abstract: Recently, we reported that a native Fasciola hepatica fatty acid binding protein (FABP) termed Fh12 is a powerful anti-inflammatory protein capable of suppressing the LPS-induced expression of inflammatory markers in vivo and in vitro. Because the purification of a protein in native form is, in many situations not cost-beneficial and unsuitable for industrial grade scale-up, this study accomplished the task of optimizing the expression and purification of a recombinant form of FABP (Fh15). Additionally, we asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
4
30
0
Order By: Relevance
“…The accurate identification of the molecules responsible for the anti-inflammatory effect is underway, but suitable candidates are molecules previously identified in FhEVs, like FABPs ( Cwiklinski et al, 2015 ), which have been shown to induce anti-inflammatory response in animal models by diminishing the levels of TNFα ( Ramos-Benitez et al, 2017 ). Other exosome-contained molecules like miRNAs represent potential candidates as they may act as immunomodulators of the intestinal innate immune response ( Buck et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accurate identification of the molecules responsible for the anti-inflammatory effect is underway, but suitable candidates are molecules previously identified in FhEVs, like FABPs ( Cwiklinski et al, 2015 ), which have been shown to induce anti-inflammatory response in animal models by diminishing the levels of TNFα ( Ramos-Benitez et al, 2017 ). Other exosome-contained molecules like miRNAs represent potential candidates as they may act as immunomodulators of the intestinal innate immune response ( Buck et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A different mechanism is deployed by the immunomodulatory ES protein Fh12 (and its recombinant form, Fh15) from the liver fluke Fasciola hepatica . The Fh12 and Fh15 proteins induce alternative activation in human monocyte-derived macrophages (Mo-Macs), suppress macrophage activation by TLR2, TLR4, TLR5, and TLR8 ligands, and inhibit inflammatory cytokine production in septic shock ( Ramos-Benítez et al., 2017 ). They bind to the TLR4 cofactor CD14 and reduce its expression, mediating suppression of TLR4 responses.…”
Section: Main Textmentioning
confidence: 99%
“…Investigations into their anti-inflammatory properties demonstrated that the 12 kDa Fh12 product reduced pro-inflammatory cytokine production in the LPS-induced model of murine sepsis ( 45 ). Similarly, the 14.5 kDa Fh15 molecule attenuated production of IL-1β and TNF-α in human THP-1 macrophages ( 46 ). In a murine model of sepsis, Fh15 treatment was associated with a significant decrease in circulating cytokines ( 46 ).…”
Section: Fasciola Hepatica Excretory-secretory Productsmentioning
confidence: 99%
“…Similarly, the 14.5 kDa Fh15 molecule attenuated production of IL-1β and TNF-α in human THP-1 macrophages ( 46 ). In a murine model of sepsis, Fh15 treatment was associated with a significant decrease in circulating cytokines ( 46 ).…”
Section: Fasciola Hepatica Excretory-secretory Productsmentioning
confidence: 99%